Ճեմարանի կրթական բարեփոխումները Ն. Ս. Օ. Տ. Տ. Գարեգին Բ. Ամենայն Հայոց կաթողիկոսի օրոք (2010-ական թվականներ) - Քալաշյան, Ավետիս (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
На основе анализа фактического материала в статье исследуется процесс образовательных перемен духовной академии «Геворкян» Первопрестольного Святого Эчмиадзина при Католикосе Всех Армян Гарегине II в 2010-х годах. Показывается, что в результате последовательной преобразовательной деятельности Гарегина II в Духовной академии, во-первых, было введено двухуровневое обучение (бакалавриат, магистратура), а учебные программы бакалавриата и магистратуры в своей концептуальной основе полностью стали соответствовать армянским государственным и европейским образовательным стандартам. Вследствие этого Духовной академии было дано право осуществлять бессрочные образовательные программы «бакалавра» и «магистра» по аккредитованной специальности «богословие». Во-вторых, были созданы все основания для повышения уровня профессиональной подготовки выпускников, была основана программа послевузовского профессионального образования (аспирантская подготовка). В-третьих, вследствие вышеназванных перемен Духовная академия «Геворкян» стала научно-образовательным и научно-исследовательским центром по аккредитованной специальности «богословие», чем был сделан существенный шаг для дальнейшей интеграции в единое европейское образовательное пространство. И, в-четвертых, ВАК РА дал Духовной академии разрешение на открытие специализированного совета по защите кандидатской диссертации по специальности «богословие». This article is an investigation of educational reforms undertaken under the leadership of His Holiness Karekin II, Catholicos of All Armenians, at the Gevorkian Theological Academy of the Mother See of Holy Etchmiadzin during the decade commencing in 2010. It demonstrates that during the Pontificate of the Catholicos of All Armenians and as a result of His Holiness’ reforms, the two-degree academic program was introduced, namely, baccalaureate and master’s programs, and the contents of the academic program were made to conform to the requirements of both the authorities of the Republic of Armenia and the standards of the European integrated educational program. As a result of these reforms, the Academy was granted accreditation, with no time limits, to undertake Bachelor’s and Master’s degree programs with the specialization of theology; secondly, measures were taken to ensure a higher level of competence among the graduates, and the Academy was able to lay the foundations of postgraduate studies; thirdly, as a result of the preceding steps, the Academy, now accredited as a specialized institution, became a center for scholarly, educational and research activities, which was a major step in its integration into the European integrated educational space; fourthly, a specialized committee was established by the Supreme Certifying Commission to oversee and supervise the process of conferring PhD degrees in theology.
Keywords: Հայոց եկեղեցի; Կրոնական կրթութիւն